Differences in the level of literacy between Minoan and Mycenaean societies in the light of the analysis of types and probable use of inscribed objects - Zadka, Małgorzata (Lingua Posnaniensis, 2012)
The aim of this paper is to present the suspected differences in the level of literacy between Minoan and Mycenian populations. Through the analysis of the number and type of preserved objects, which were inscribed in Linear A and comparing the results with the type of artefacts inscribed in Linear B we are able to define the original function of script in both cultures. The preserved epigraphic and archaeological material may indicate that the writing skills were more prevalent in the earlier Minoan than in the Mycenaean era.